Neurologic Deficits Including Auditory Loss and Recovery of Function in Horses with Temporohyoid Osteoarthropathy. (29th October 2015) - Aleman, M.; Spriet, M.; Williams, D.C.; Nieto, J.E.
Abstract : Background: Auditory loss is a common deficit in horses with temporohyoid osteoarthropathy (THO), however, recovery of function is unknown. Hypothesis/Objectives: To investigate neurologic function with emphasis in audition in horses with THO after treatment. To describe anatomical alterations of the petrous temporal bone that might result in auditory loss. Animals: Twenty‐four horses with a clinical diagnosis of THO. Methods: Prospective study. A brainstem auditory evoked response (BAER) study was done as part of the criteria for inclusion in horses with a clinical diagnosis of THO from the years of 2005 to 2014. Physical and neurologic status and BAER findings were recorded. Brainstem auditory evoked response variables were compared by using Wilcoxon sign test. Fisher's exact test was also used. Significance was set at P < 0.05. Results: The most common signs included auditory loss (100% of horses), vestibular and facial nerve dysfunction (83%), and exposure ulcerative keratitis (71%). Concurrent left laryngeal hemiparesis was observed in 61% of horses through endoscopy. Auditory dysfunction was bilateral in 50% of the cases (complete and partial), and unilateral affecting more commonly the right ear (R = 8, L = 4). Short‐ and long‐term follow‐up revealed persistent auditory loss in all horses based on abnormal response to sound, and further confirmed through a BAER in 8 horses. Conclusions and Clinical Importance: Auditory dysfunction appears to be a permanent neurologic deficit in horses diagnosed with THO despite overall neurologic improvement.